2012
DOI: 10.1177/2158244012464976
|View full text |Cite
|
Sign up to set email alerts
|

A Cultural Models Approach to Osteoporosis Prevention and Treatment

Abstract: This article identifies cultural models of osteoporosis, as shared by community-dwelling older women in southeastern Australia, and compares these with cultural knowledge conveyed through social marketing. Cultural models are mental constructs about specific domains in everyday life, such as health and illness, which are shared within a community. We applied domain analyses to data obtained from in-depth interviews and stakeholder-identified print materials. The response domains identified from our case studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In a prospective cohort study of 240 older participants, those who experienced high levels of depressive symptoms prior to a medical event (hip fracture, stroke and heart attack), had a poorer likelihood of recovery in activities of daily living 27. Finally, a recent study using cultural models approach to understand how older women viewed osteoporosis reported that experiencing a fracture coincided with the acknowledgement of ‘getting older’ 28. Thus, we may expect a fracture to increase the likelihood of depression for some older women.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study of 240 older participants, those who experienced high levels of depressive symptoms prior to a medical event (hip fracture, stroke and heart attack), had a poorer likelihood of recovery in activities of daily living 27. Finally, a recent study using cultural models approach to understand how older women viewed osteoporosis reported that experiencing a fracture coincided with the acknowledgement of ‘getting older’ 28. Thus, we may expect a fracture to increase the likelihood of depression for some older women.…”
Section: Discussionmentioning
confidence: 99%
“…Given that osteoporosis often remains undetected until after a fragility fracture occurs [9], it is plausible that non-participation related to disinterest may be due to a lack of awareness of the disease. Osteoporosis has also been identified as a condition with ‘low salience’ among the lay and medical communities – there exists a level of ambivalence and unconcern about osteoporosis in individual patients and the general population [10,11]. Other factors that hampered interest may have been that certain attributes of the study were not salient or appealing enough to provide motivation to participate [12]; people may not see a personal gain from participating or feel disillusioned with scientific research on the whole [13].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from time constraints, which explained 13% of nonparticipation in the current study, Galea’s reasons for non-participation may have been encompassed in our disinterested category. Otmar and colleagues 24 investigated cultural models of osteoporosis in the same study region as the current study, and showed that osteoporosis is considered to be of low salience in the community which might explain the disinterest shown by some of the individuals approached to participate in the study. Reporting of disinterest for the reason for non-participation was influenced by age, whereby younger adults were more likely to cite it.…”
Section: Discussionmentioning
confidence: 90%